Biodegradability enhancement and sequential treatment of real chemical industry wastewater by chemical coagulation and Electro-Fenton processes - Guvenc, Senem Yazici; Can-Guven, Emine; Cifci, Deniz Izlen; Varank, Gamze (ELSEVIER SCIENCE SA, 2023)
A sequential treatment with chemical coagulation in the first step and Electro-Fenton (EF) in the second step was applied to chemical industry wastewater. By coagulation using Poly Aluminum Chloride (PAC) as a coagulant, 57.5% chemical oxygen demand (COD), 96.8% total suspended solids (TSS), and 90.5% color index (CI) removal were obtained. In the EF process applied after chemical coagulation, the design parameters were optimized by the central composite design. Two quadratic models of the four factors were established with the COD and CI as two responses. Optimized conditions of the EF were pH 2.5, Fe2+ dose 5 mM, applied current 1 A, and reaction time 60 min. Under these conditions, the COD removal from the validation experiments was 63.5%. In total, 84.5% COD removal was achieved with the two-step treatment. By extending the reaction time in EF to ensure the discharge limits, 89.5% COD removal was reached, and the COD concentration decreased to 193 mg/L after 240 min. At the same time, the 5-day biochemical oxygen demand (BOD5)/COD ratio increased from 0.1 to 0.57 after 240 min. Consequently, the discharge limit was provided and the biodegradability was improved.
Keywords: Biodegradability; Coagulation; Industrial wastewater; Poly aluminum chloride; Sequential treatment; OXIDATION PROCESSES; ENERGY-CONSUMPTION; PHOTO-FENTON; COD REMOVAL; ELECTROCOAGULATION; OPTIMIZATION; SLUDGE; CARBON; DEGRADATION; COMBINATION; Energy & Fuels; Engineering